Back pain and osteoporosis - A. I. Isaikin; O. Yu. Isaikina; T. I. Shadyzheva; Yu. M. Shor; M. S. Kachanovsky (Неврология, нейропсихиатрия, психосоматика, 2019)
The aging process is accompanied by a structural change and a decrease in the functional activity of organs and tissues, including the bone, with the development of osteoporosis (OP).Objective: to assess the characteristics of pain syndrome in OP patients with nonspecific chronic vertebrogenic lumbar ischialgia (CLI).Patients and methods. Sixty elderly patients with CLI in the presence and absence of OP were examined. All the patients underwent dual-energy X-ray absorptiometry and ultrasound to diagnose the degree of OP and spinal deformity; a flexible rod was used according to the method described by M.A. Kathleen to estimate the angle of kyphosis, lordosis, and scoliosis. The investigators determined pain intensity by a numerical rating scale, the presence of a neuropathic pain component by the DN4 pain scale, the level of anxiety and depression by the Hospital Anxiety and Depression Scale, cognitive status by the Montreal Cognitive Function Rating Scale, the degree of disability by the Oswestry questionnaire, and quality of life by the SF-12 Health Survey.Results and discussion. Our study showed that OP alone is not a cause of CLI in elderly patients. There were no statistically significant differences in the sources and intensity of pain, the degree of anxiety and depressive disorders, impaired quality of life, cognitive status, and degree of disability in patients with chronic lumbar pain syndrome in the presence and absence of OP. Vertebral deformity resulting from OP leads mainly to an obvious poor posture with an increase in thoracic kyphosis, straightening of lumbar lordosis, and S-curve lumbar and thoracic scoliosis, which can also cause secondary muscle spasm.Patients with back pain in the presence of OP are treated in accordance with the general principles of management of patients with non-specific back pain, but taking into account the underlying disease. The paper presents current recommendations for the treatment of nonspecific back pain, for the management of patients with OP, as well as the updated clinical recommendations for the prevention of fractures in OP and osteopenia.Conclusion. Patients with OP are noted to have predominantly chronic musculoskeletal pain in the presence of severe spinal deformity, but the level of this evidence is very low. The features of pain syndrome in patients with nonspecific vertebrogenic chronic lumbar ischialgia in the presence of OP call for further investigations.